Jealousy Protest: Ontogeny in Accord With the 9-Month Period of Human Gestation. (2nd May 2016) - Hart, Sybil L.
In this article, nascent jealousy's ultimate foundation is theorized as an adapted psychological mechanism that evolved in the environment of evolutionary adaptedness (EEA) to prepare 1-year-olds for defending against premature weaning upon the closely spaced birth of a sibling. This position rests on evidence that nascent jealousy is expressed through jealousy protest, a constellation of caregiver-directed protests and bids for exclusive attention, and evidence that its onset occurs at approximately 9 months of age. Given that the period of human gestation is 9 months, we propose that jealousy protest's form and timing were compelled by the possibility that the end of an infant's first year could be met by competition with a newborn sibling. That possibility placed infants at risk of malnutrition and mortality due to entailing the loss of exclusive access to mother's milk, while infants were at an age when they were still heavily reliant on breast milk for survival. At this juncture, threat posed by the birth of a sibling was compounded by conditions of the EEA, where the sole viable source of breast milk was an infant's mother, and her supply of milk was sufficient for sustaining only one child at a time. We conclude by offering suggestions for future research and discuss implications for the theory of parent–offspring conflict as a foundation of adaptations in children.